4YOUTH TAKAFUL IN ISLAMIC INSURANCE INDUSTRY: TECHNOLOGY AND LIFESTYLES - Muslimah Mustakim; Sarah Nur Saadah Mohd Zameri; Siti Khadijah Ngabdullah; Mohammad Firdaus Mohammad Hatta; Mohamad Nizam Jaafar (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Malaysia is on track to becoming the world’s leading global finance hub. Malaysia remains the leader among 56 countries for Islamic financial institutions. However, Takaful is said to be left behind, not only to the other Islamic finance players, but also to the conventional insurance. Previous studies identified low penetration rate of Takaful as one of the factors. Takaful operators are unable to provide competitive products in the market, due to their limited funds. Most rejections came from employed youth. With their lifestyles, peak of health and limited income, Takaful products are not their priorities. Thus, a need to attract this group of people must be done to increase the penetration rate and increase the contribution funds. The study is done to fulfil five objectives, which were to come out with a Takaful product that attracts the youngsters, increase the funds of Takaful operators, create a product that suits and can give benefit to the young people, promote healthy lifestyle among youngsters and promote the growth of Takaful industry in Malaysia. 4YOUth Takaful combines technology and lifestyles of youths through an apps that connects Takaful operators, online shopping platforms, selected retailers and the youth Takaful participants. Scoring system is used to convert the purchase of health-related products into points which later will be used to reduce the monthly contributions of Takaful. Not only enabling youth to have financial protection from an early stage while maintaining their desired lifestyles, 4YOUth Takaful also encourages healthy lifestyles.